The Effect of Puppet-Based Learning Media on Elementary School Students' Listening Comprehension Skills - Natalino Leonel de Carvalho; Nurul Mastura; Hidayat Hidayat; Eka Yulianti (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study aimed to examine the effect of using wayang media on the story-listening skills of third-grade elementary school students. The research employed a quantitative approach with a quasi-experimental nonequivalent control group pretest-posttest design involving 40 students, consisting of 20 students in the experimental group and 20 students in the control group. The experimental group learned story listening through wayang media, whereas the control group received conventional instruction using the same story material. Data were collected using a multiple-choice listening comprehension test measuring students’ understanding of characters, setting, sequence of events, explicit information, implicit information, and moral messages. The descriptive results showed that the experimental group increased from a pretest mean of 72.75 to a posttest mean of 85.75, while the control group increased from 64.00 to 78.50. Because the experimental group had a higher initial score than the control group, the findings were interpreted cautiously. The raw gain was 13.00 in the experimental group and 14.50 in the control group, while the normalized gain was 0.48 and 0.40, respectively. The independent sample t-test on posttest scores showed a statistically significant difference, t(38) = 2.873, p = 0.007, mean difference = 7.25, with Cohen’s d = 0.91. These findings indicate that wayang media has positive potential to support students’ story-listening comprehension, although the baseline difference limits the strength of causal inference. Wayang can be considered a contextual low-tech visual-narrative medium that integrates Indonesian cultural elements into language learning.